Information and Communication Technology Leadership of School Administrators in Thailand - Amnat Apsorn; Boonchan Sisan; Pariyaporn Tungkunanan (My University, 2019)
This research aims to study the components and to do confirmatory factor analysis, and study the perceptions of ICT leadership of school administrators in Thailand.The results indicate that eight components of information and communication technology (ICT) leadership: developing a vision and administrative plans for the use of ICT in schools, establishing strategies for promoting teachers' and students' use of technology in instruction; developing plans for improving teachers' and supporting staff's technological skills; managing, supporting and facilitating an atmosphere conducive to the use of ICT and providing information technology (IT) resources; learning about meeting ICTrelated challenges with prudence and care; acting as a role model in applying ICT to daily personal and professional matters; sharing knowledge, opening up opportunities and creating an ICT culture in schools in order to develop a learning community, and overseeing and doing follow-up on data storage and data updates for the benefit of decision making and problem solving.Confirmatory Factor Analysis suggests that the components of IT and communication leadership correspond significantly with empirical data and school administrators' perceptions of ICT leadership for use to develop guidelines for efficiently and effectively improving the capacity of ICT school leaders.
Keywords: Online and Blended Learning